Genetic Algorithm (GA) for Multiprocessors Scheduling - Mohd Jufri, Sainuddin; Izwan Suliman, Saiful; Asri Mansor, Mohd; Wati Mohamad Yusof, Yuslinda; Mohamad, Roslina; Shahbudin, Shahrani; Kassim, Murizah (International Journal of Engineering and Technology, 2018)
In a multiprocessors environment, an algorithm is used to effectively delegate tasks to the processors. The algorithm act as the resource distributor and controller to ensure that the processors are equally utilized thus optimizing the usage of the processors. Thus, the objectives of the study are to replicate the Genetic Algorithm (GA) and use the algorithm to shorten the timespan for the parallel task to be completed. The algorithm has the ability to improve and find the optimum solution based on the population needs. Hence, C++ is used as the platform for the simulation. Experimental results validate that the designed program has the ability to replicate the GA in achieving the objectives of the study.Â